The role of the institutional environment in regulating innovative activities in the industry - Herasymenko, T.; Герасименко, Т. В.; Bieloborodova, M.; Бєлобородова, М. В.; Bezuhla, L.; Безугла, Л.С.; Atamas, Oleksandr; Атамас, Олександр Петрович; Makukha, Yu.; Макуха, Ю. М. (Національний гірничий університет, 2025)
Purpose. To determine the factors of innovative development of industrial enterprises of Ukraine in conditions of economic destabilization, based on taking into account the asymmetric influence of the institutional environment, human capital and market development, for further identification of priority areas of state policy. Methodology. To assess the impact of the institutional environment, human capital and market conditions on the results of innovation activity, a multifactor econometric model was applied, which allows for the identification of asymmetries in the impact of different components on innovation efficiency. Statistical analysis of the Global Innovation Index indicators was used to identify key environmental factors that stimulate or inhibit the innovative activity of industrial enterprises. Findings. The key indicators of innovation activity in Ukraine were analyzed, and their compliance with the target challenges was established. The dynamics of the Global Innovation Index and its components were assessed. Key areas requiring improvement were identified, and the indicators of international ratings relatively to the formation of Ukrainian innovation ecosystem were assessed. The main results of the study indicate the presence of an imbalance in the influence of the institutional environment and human capital on innovation efficiency, which indicates the fragmentation of policy and insufficient integration of scientific developments into industry. At the same time, market mechanisms show a positive impact, emphasizing the importance of investment activity, access to financing and developed innovation infrastructure. Originality. An economic and mathematical model is constructed of the multifactorial efficiency of state regulation of the innovative activity of industrial enterprises of Ukraine, which considers the asymmetric influence of key factors: the negative impact of the institutional environment and human capital, as well as the positive impact of market development. The proposed approach allows assessing the relationship between the conditions for innovative activity and their performance as well as identifying priority areas of state policy. Practical value. The developed model can serve as a tool for monitoring the effectiveness of regulatory measures and determining priority areas of economic stimulation of innovations. The results obtained can be used to implement effective mechanisms of state regulation of innovation activity in conditions of limited resources, martial law and economic instability. Мета. Визначення факторів інноваційного розвитку промислових підприємств України в умовах економічної дестабілізації на основі врахування асиметричного впливу інституційного середовища, людського капіталу й розвитку ринку, для подальшої ідентифікації пріоритетних напрямів державної політики. Методика. Для оцінки впливу інституційного середовища, людського капіталу й ринкових умов на результати інноваційної діяльності застосована багатофакторна економетрична модель, що дозволяє виявити асиметрії у впливі різних компонентів на інноваційну ефективність. Використано статистичний аналіз показників Глобального індексу інноваційності для ідентифікації ключових факторів середовища, що стимулюють або стримують інноваційну активність промислових підприємств. Результати. Проаналізовані ключові показники інноваційної діяльності в Україні та встановлена їх відповідність цільовим викликам. Оцінена динаміка Глобального інноваційного індексу та його складових. Визначені ключові напрями, що потребують удосконалення, оцінені показники міжнародних рейтингів відносно формування інноваційної екосистеми України. Основні результати дослідження свідчать про наявність дисбалансу у впливі інституційного середовища й людського капіталу на інноваційну ефективність, що вказує на фрагментарність політики та недостатню інтеграцію наукових розробок у промисловість. Водночас ринкові механізми показують позитивний вплив, підкреслюючи важливість інвестиційної активності, доступу до фінансування й розвиненої інноваційної інфраструктури. Наукова новизна. Полягає у розробці економіко-математичної моделі багатофакторної ефективності державного регулювання інноваційної діяльності промислових підприємств України, що враховує асиметричний вплив ключових факторів: негативний вплив інституційного середовища й людського капіталу, а також позитивний вплив розвитку ринку. Запропонований підхід дозволяє оцінити взаємозв’язок між умовами для інноваційної діяльності та їхньою результативністю, а також ідентифікувати пріоритетні напрями державної політики. Практична значимість. Розроблена модель може слугувати інструментом для моніторингу ефективності регуляторних заходів і визначення пріоритетних напрямів економічного стимулювання інновацій. Отримані результати можуть бути використані для впровадження ефективних механізмів державного регулювання інноваційної діяльності в умовах обмежених ресурсів, воєнного стану та економічної нестабільності.
Роль інституційного середовища в регулюванні інноваційної діяльності промисловості
Keywords: innovations; інновації; industrial enterprises; промислові підприємства; state regulation; державне регулювання; investments; інвестиції; innovation market; ринок інновацій